The Autonomous Enterprise : Powered by AI - Burnett, Sarah (BCS, The Chartered Institute for IT, 2022)
The journey towards the autonomous enterprise has begun; there are already companies operating in a highly automated way, and with intelligent solutions offering compelling returns on investment, more organisations will be joining their ranks. With a workforce of machines that are augmented by humans, the autonomous enterprise will turn the current organisational model on its head. Every corporate decision-maker will need to understand the new model, learn about the possibilities and the opportunities it presents, the risks, the shifting competitive landscape, and how to navigate the journey of change. This book is your guide to this innovation, presenting the concepts in real world contexts by covering the art of the possible today and providing glimpses into the future of business.